Mixed Acinar-Endocrine Carcinoma of the Pancreas with Intraductal Growth into the Main Pancreatic Duct : Report of a Case - Kobayashi, Shinjiro; Asakura, Takeshi; Ohike, Nobuyuki; Enomoto, Takeharu; Sakurai, Joe; Koizumi, Satoshi; Watanabe, Taiji; Nakano, Hiroshi; Otsubo, Takehito (Surgery today (Tokyo, Japan), 2010)
The patient was a 75-year-old asymptomatic man, in whom a tumor mass in the pancreatic tail had been found 6 months earlier. Computed tomography revealed a mass 7 cm in diameter, and an enhancement with contrast medium was observed at the periphery and partially inside the mass, but not in most parts of the tumor. Endoscopic retrograde cholangiopancreatography showed a filling defect in the main pancreatic duct. A distal pancreatectomy was performed because of the possibility of a malignant tumor. The tumor consisted of a lobular invasive growth component and a component with intraductal growth into the main pancreatic duct, and histologically the tumor cells had solid acinar to partially trabecular/tubular patterns. Trypsin (an acinic cell marker) expression was widely observed, followed by the expression of chromogranin A (an endocrine cell marker) in about 30% of the tumor cells. The tumor was diagnosed as mixed acinar-endocrine carcinoma according to the WHO classification.